A class of generalized mixed variational–hemivariational inequalities II: Applications. (December 2019) - Migórski, Stanisław; Bai, Yunru; Zeng, Shengda
Abstract: In this paper we continue the study on generalized mixed variational–hemivariational inequalities which has been recently carried out in Bai et al. (2019). There, several abstract results on existence, uniqueness, and stability of solution are established. To illustrate the applicability of these results, we present two applications. The first application is an elliptic system driven by mixed boundary conditions and a nonhomogeneous partial differential operator. The second one is a frictionless elastic contact model with a unilateral boundary condition and the constitutive law involving the generalized subgradient inclusion.